Medium-Sized Cities as Peripheral Centers: Cooperation, Competition and Hierarchy in Shrinking Regions - Kühn Dipl. Ing., Manfred; Milstrey, Ulrike (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
Research and policy assume that inter-municipal cooperation is necessary to strengthen the role of medium-sized cities as regional centers in shrinking and peripheral regions and to ensure that services of general interest are maintained. Against this background, the article examines how medium-sized cities manage to position themselves in peripheral regions between the poles of re-centralization and peripheralisation. We discuss how inter-municipal cooperation, competition and hierarchies interact. Using the concept of Regional Governance as a framework for the analysis the questions are investigated empirically based on two case studies: firstly, using the example of the city triangle Altmark (Saxony-Anhalt), which is a polycentric network of cities, consisting of the city of Stendal and two neighbouring towns. Secondly, the location initiative Southwest-Pfalz (Rheinland-Pfalz) is scrutinized, an urban-rural cooperation between the city of Pirmasens and the district Southwest-Pfalz. The results indicate that both the pressure for cooperation and the need for competition are increasing for local actors. Finally we assume that inter-municipal cooperation only works under specific conditions and draw conclusions for regional planning, state and urban policy.
Keywords: Peripheralisation; Re-centralization; Medium-sized cities; Inter-municipal cooperation; Competition; Hierarchy